2022
DOI: 10.1111/birt.12692
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of midwifery care in English prisons

Abstract: Background: In the United Kingdom (UK), all prisoners must receive healthcare equivalent to that available in the community. However, evidence suggests that equality in healthcare provision for perinatal women in UK prisons is not always achieved. The aim of this research was to examine pregnant women prisoners' and custody staffs' experiences and perceptions of midwifery care in English prisons. Methods:A qualitative approach based on institutional ethnography was used to research women's experiences in three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Of the sixteen included papers, six were from the United States of America (USA) (Ferszt & Clarke, 2012 ; Hackett, 2017 ; Kelsey et al, 2017 ; Kotlar et al, 2015 ; Kramer et al, 2023 ; Nair et al, 2021 ), four from the United Kingdom (UK) (Abbott, 2018 ; Abbott et al, 2023 ; Albertson et al, 2012 ; Bard et al, 2016 ), three from Iran (Alirezaei & Roudsari, 2020 , 2022a , 2022b ), two from Canada (Ifeonu et al, 2022 ; Kirubarajan et al, 2022 ), and one from Australia (Baldwin et al, 2020a ). Five of the included papers were literature reviews (Alirezaei & Roudsari, 2022a ; Baldwin et al, 2020a ; Bard et al, 2016 ; Kirubarajan et al, 2022 ; Nair et al, 2021 ), one a mixed methods study (Ferszt & Clarke, 2012 ), one a quantitative study (Kelsey et al, 2017 ), five qualitative studies (Abbott, 2018 ; Abbott et al, 2023 ; Alirezaei & Roudsari, 2022b ; Hackett, 2017 ; Ifeonu et al, 2022 ), two policy analyses (Alirezaei & Roudsari, 2020 ; Kramer et al, 2023 ), one a multi-component consultation paper (Albertson et al, 2012 ), and one a report (Kotlar et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the sixteen included papers, six were from the United States of America (USA) (Ferszt & Clarke, 2012 ; Hackett, 2017 ; Kelsey et al, 2017 ; Kotlar et al, 2015 ; Kramer et al, 2023 ; Nair et al, 2021 ), four from the United Kingdom (UK) (Abbott, 2018 ; Abbott et al, 2023 ; Albertson et al, 2012 ; Bard et al, 2016 ), three from Iran (Alirezaei & Roudsari, 2020 , 2022a , 2022b ), two from Canada (Ifeonu et al, 2022 ; Kirubarajan et al, 2022 ), and one from Australia (Baldwin et al, 2020a ). Five of the included papers were literature reviews (Alirezaei & Roudsari, 2022a ; Baldwin et al, 2020a ; Bard et al, 2016 ; Kirubarajan et al, 2022 ; Nair et al, 2021 ), one a mixed methods study (Ferszt & Clarke, 2012 ), one a quantitative study (Kelsey et al, 2017 ), five qualitative studies (Abbott, 2018 ; Abbott et al, 2023 ; Alirezaei & Roudsari, 2022b ; Hackett, 2017 ; Ifeonu et al, 2022 ), two policy analyses (Alirezaei & Roudsari, 2020 ; Kramer et al, 2023 ), one a multi-component consultation paper (Albertson et al, 2012 ), and one a report (Kotlar et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Generally, these packs include additional sources of nutrition such as extra food (e.g., bread) and/or milk or milk supplements. The two studies by Abbott ( 2018 ) and Alirezaei & Roudsari ( 2022b ) discussed how women could ‘buy up’ extra foods, but lack of funds often limited this (Abbott, 2018 ), particularly when they were not allowed to work (Alirezaei & Roudsari, 2022b ), and the foods available to buy were often unhealthy (Abbott, 2018 ). A complete lack of extra food offerings was lamented in other studies (Albertson et al, 2012 ; Alirezaei & Roudsari, 2022b ; Kirubarajan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite international and national requirements for equivalent care to what is available in community, existing research in the field of prison perinatal health has found delays and gaps in care and poor neonatal outcomes associated with pregnancy in prison 1. This study by Abbott et al 2 focuses on incarcerated patient access to midwifery services, the leading type of perinatal care provision in the UK, and prison staff understanding of both midwifery care and the distinct need for care among pregnant people.…”
Section: Contextmentioning
confidence: 99%